Using saturated absorption spectroscopy on acetylene-filled hollow-core fibers for absolute frequency measurements - Knabe, Kevin (Kansas State University, 2010)
Current portable near-infrared optical frequency references offer modest accuracy and instability compared to laboratory references. Low pressure reference cells are necessary to realize features narrower than the Doppler broadened overtone transitions, and most setups to date have occurred in free-space. Hollow-core photonic crystal fibers offer a potential alternative to free-space setups through their small cores (~10’s of µm) and low-loss guidance. Furthermore, HC-PCF can be made into fiber cells that could be directly integrated into existing telecommunications networks. Efforts were made to fabricate these fiber cells with a low pressure of molecules trapped inside, but this has proven to be quite challenging. Therefore, investigation of these fibers is conducted by placing the ends of the fiber inside vacuum chambers loaded with acetylene (12C2H2). The linewidths of several P branch transitions (near 1.5 µm) are investigated as a function of acetylene pressure and optical pump power in three different HC-PCFs. Frequency modulation spectroscopy is then implemented on the acetylene-filled HC-PCF to generate sub-Doppler dispersion features that are useful for frequency stabilization using standard servo electronics. Instability and accuracy of this near-IR optical reference were then determined by analysis of heterodyne experiments conducted with frequency combs referenced to a GPS-disciplined rubidium oscillator. The instability and accuracy of this HC-PCF reference are within an order of magnitude of free-space experiments, as expected based on the ratio of linewidths observed in the two experiments. Therefore, HC-PCF has been shown to be suitable for potential frequency references. Further work is necessary to fabricate gas fiber cells with high optical transmission and low molecular contamination.
Keywords: Near infrared molecular optical frequency reference; Hollow core photonic crystal fiber; Physics, Atomic (0748); Physics, Molecular (0609); Physics, Optics (0752)